Is trade in electrical and electronic products sensitive to IPR protection?: Evidence from China’s exports - Kabir, M.; Salim, Ruhul (2015)
© 2015 Taylor & Francis This article attempts to provide the first empirical evidence on the effect of intellectual property rights (IPRs) on China’s export of electrical and electronic products. It adopts a gravity model for unbalanced panel data of China’s 146 important trading partners over the period of 2002–2012. To eliminate the effects of FDI in determining the linkage between IPR and exports, the panel excludes the destination countries and territories that invest in China. The results reveal that the level of IPR protection in destination countries has a positive impact on China’s flow of exports. Further analysis on data disaggregated by IPR score demonstrates that a higher level of IPR protection in destination countries and territories is positively linked with China’s exports of these items in each of the IPR protection clusters and indicates a strong market power effect by the interplay between R&D expenditure and IPR in the destinations. Finally, both market power and market expansion effects are found to be prevalent in the destinations, as implied by the coefficient of IPR protection disaggregated by income level of China’s export destinations. The results generally resemble those in the literature that describe the linkage between IPR protection and trade flows.